Strategies in Improving Business Networks in Fried Banana Culinary Businesses - Ihsan Burhanudin; Resya Dwi Marselina; Anisa Putri; Putri Nur Alis Azizah (LPPM STMIK Mardira Indonesia, 2024)
The fried banana culinary business is the focus of this research for business strategy, with an emphasis on product quality, menu innovation, and digital marketing strategy. Maintained product quality, such as distinctive taste and visual appearance, influences consumers' positive preferences, according to sensory evaluation. The case study shows that menu innovation, especially in terms of variations in taste and presentation, is the key to the success of the fried banana culinary business. It is proven that digital marketing strategies such as special promotions and an active presence on social media can increase visibility and sales. The integration results emphasize that success in this industry requires a combination of consistent high-quality products, continuous innovation and the use of smart digital marketing strategies. The discussion acknowledges study limitations such as sample size and geographic scope, but also emphasizes the relevance of the results to the existing literature. So, to achieve long-term success in the dynamic fried banana culinary industry, the combination of these important components provides a strong foundation. They suggest maintaining product quality standards, developing an ever-changing menu, and using a more sophisticated digital marketing approach. To gain a broader understanding, further research can expand the geographic scope and involve more types of culinary businesses.